Pengaruh Konseling Kelompok terhadap Kecemasan Akademik - Qutratu’ain, Bilqis Asyifa; Ardhani, Deandra Qurrata; Natalia, Deasyandra; Nuraini, Eka Safitri (TSAQOFAH, 2025)
Academic anxiety is a common problem faced by students, this academic anxiety can interfere with student achievement and well-being if not handled properly. School counselors or BK teachers have an important role in helping and solving the academic anxiety problems inherent in these students through counseling groups. The primaly goal of this study is to provide a comprehensive overview of trends, strengths, and gaps in research in this field. This study conducts a literature review to analyze and identify various group conseling techniques effective in reducing academic anxiety demonstrates significant and effetive result in lowering levels of academic anxiety throught various group counseling techniques. This indicates that the implementation of group counseling is highly important and effective in reducing academic anxiety experienced by students.